Grouting solidification technology for fractured soft coal seams and its application in coalbed methane (coal mine gas) extraction - Guangbo, Zhang; Suian, Zhang; Wei, Jia; Xiao, Zhang; Yang, Zhang; Haoyu, Lian; Xiaohua, Lian; Huili, Fang (Frontiers in Energy Research, 2023)
This article presents an effective method for improving the structure and performance of coal rock masses, thereby facilitating coalbed methane extraction—the grouting solidification technique. A systematic review is conducted on grouting solidification materials, process methods, evaluation techniques, and other related aspects. In conclusion, it is emphasized that the grouting solidification technique requires further refinement in its system, and its continued significance in the dynamically evolving energy and coal industry is underscored. This is crucial for ensuring the efficient development and sustainable utilization of coal and coalbed methane resources.